2005
DOI: 10.1590/s0074-02762005000700012
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium restriction fragment lenght polymorphism-IS IS1245 and the simple double repetitive element polymerase chain reaction typing method to screen genetic diversity in Brazilian strains

Abstract: Simple double repetitive element polymerase chain reaction (MaDRE-PCR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our review showed that MSIs involving NTM have not been investigated to the same extent as compared to those caused by M. tuberculosis ( Table 2). Amongst the 121 mycobacterial studies identified, 26 (21.5%) examined NTM, of which 17 (14.0%) and eight (6.6%) found MSIs in humans and animals, respectively, whereas one report identified MSIs in both human (Arbeit et al, 1993;Slutsky et al, 1994;Von Reyn et al, 1995;Devallois and Rastogi, 1997;Picardeau et al, 1997;Wallace et al, 1998;Legrand et al, 2000a,b;Oliveira et al, 2000;Saad et al, 2000;Dvorska et al, 2002;Panunto et al, 2003;Ohkusu et al, 2004;De Sequeira et al, 2005;Fujita et al, 2014;García-Pedrazuela et al, 2015;Kimizuka et al, 2019) and animal (Dvorska et al, 2007;Shitaye et al, 2008;Furphy et al, 2012;Gerritsmann et al, 2014;Johansen et al, 2014;Gioffré et al, 2015;Podder et al, 2015;Davidson et al, 2016;Pfeiffer et al, 2017) populations simultaneously (Pate et al, 2008). Many early studies used pulsed field gel electrophoresis (PFGE) to identify MSIs in 14.3-100% of patients infected with MAC bacteria (Arbeit et al, 1993;Slutsky et al, 1994;Von Reyn et al, 1995;Wallace et al, 1998;Ohkusu et al, 2004).…”
Section: Non-tuberculous and Other Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Our review showed that MSIs involving NTM have not been investigated to the same extent as compared to those caused by M. tuberculosis ( Table 2). Amongst the 121 mycobacterial studies identified, 26 (21.5%) examined NTM, of which 17 (14.0%) and eight (6.6%) found MSIs in humans and animals, respectively, whereas one report identified MSIs in both human (Arbeit et al, 1993;Slutsky et al, 1994;Von Reyn et al, 1995;Devallois and Rastogi, 1997;Picardeau et al, 1997;Wallace et al, 1998;Legrand et al, 2000a,b;Oliveira et al, 2000;Saad et al, 2000;Dvorska et al, 2002;Panunto et al, 2003;Ohkusu et al, 2004;De Sequeira et al, 2005;Fujita et al, 2014;García-Pedrazuela et al, 2015;Kimizuka et al, 2019) and animal (Dvorska et al, 2007;Shitaye et al, 2008;Furphy et al, 2012;Gerritsmann et al, 2014;Johansen et al, 2014;Gioffré et al, 2015;Podder et al, 2015;Davidson et al, 2016;Pfeiffer et al, 2017) populations simultaneously (Pate et al, 2008). Many early studies used pulsed field gel electrophoresis (PFGE) to identify MSIs in 14.3-100% of patients infected with MAC bacteria (Arbeit et al, 1993;Slutsky et al, 1994;Von Reyn et al, 1995;Wallace et al, 1998;Ohkusu et al, 2004).…”
Section: Non-tuberculous and Other Mycobacteriamentioning
confidence: 99%
“…Though the presence of IS1245-RFLP may be supplemented using additional methods, studies have shown it alone is capable of identifying 2.6-100% of NTM MSIs in samples from human subjects, some with HIV-AIDS (Supplementary Table 2) (Picardeau et al, 1997;Saad et al, 2000;Dvorska et al, 2002;Panunto et al, 2003;Pate et al, 2008). In addition, a study examined 41 samples from 14 AIDS patients using MaDRE-PCR, which found four cases with multiple banding patterns, though re-evaluation using IS1245-RFLP only confirmed two as M. avium MSIs (De Sequeira et al, 2005). Based on the reports mentioned above, the feasibility of using IS1245-RFLP as a screening method for detecting NTM MSIs warrants further evaluation.…”
Section: Non-tuberculous and Other Mycobacteriamentioning
confidence: 99%
“…New techniques include diagnostic deoxyribonucleic acidribonucleic acid (DNA-RNA) and polymerase chain reaction (PCR) tests for specific mycobacterial genes (9,10,11,13,15,20,21,25,28,29). Polymorphism restriction analysis (PRA) is used for identifying mycobacterial species and subspecies (8,10,42,55). Another DNA cleavage technique involves pulsed-field gel electrophoresis which identifies subspecies within a group.…”
Section: Diagnosismentioning
confidence: 99%